What is special about enterprise performance in North-East People's Republic of China? Dynamics of privatization, profitability and productivity during the reform era - Geng Xiao (Asian Development Bank Institute (ADBI), 2005)
Using the annual survey on large and medium-sized industrial enterprises in People's Republic of China (henceforth PRC) by the National Bureau of Statistics, this paper examines enterprise performance in north-east PRC. It shows clearly that the privatization of SOEs in the north-east region during 1995-2002 is rapid and often more aggressive than in the rest of PRC. The improvement in profitability and productivity of enterprises in the northeast PRC is also as significant as in the rest of PRC. Reforms in the north-east region have led to dramatic changes in the allocation of capital and labor, largely consistent with the national trend. Using regression analysis on the firm-level panel data, the study is able to measure and explain the differences in firm productivity and profitability across time, region, ownership, and market conditions, and to identify the remaining performance gaps that are specific only to the north-east region. The results of this study indicate that while the northeast region should continue the standard market-oriented reforms, such as privatization, encouraging market competition, and attracting FDI, it should also work hard to catch up in institutional reforms that could improve its local business environment since the performance gaps that are due specific to its location are still quite large.
Keywords: 330; Wirtschaftsreform; Privatisierung; Wirkungsanalyse; Unternehmensentwicklung; Rentabilität; Produktivität; China (Nordost)